O‐GlcNAcylation promotes fatty acid synthase activity under nutritional stress as a pro‐survival mechanism in cancer cells. Issue 9 (9th February 2022) - Wong, Yin‐Kwan; Wang, Jigang; Lim, Teck Kwang; Lin, Qingsong; Yap, Celestial T.; Shen, Han‐Ming
Abstract: Protein O‐GlcNAcylation is a specific form of protein glycosylation that targets a wide range of proteins with important functions. O‐GlcNAcylation is known to be deregulated in cancer and has been linked to multiple aspects of cancer pathology. Despite its ubiquity and importance, the current understanding of the role of O‐GlcNAcylation in the stress response remains limited. In this study, we performed a quantitative chemical proteomics‐based open study of the O‐GlcNAcome in HeLa cells, and identified 163 differentially‐glycosylated proteins under starvation, involving multiple metabolic pathways. Among them, fatty acid metabolism was found to be targeted and subsequent analysis confirmed that fatty acid synthase (FASN) is O‐GlcNAcylated. O‐GlcNAcylation led to enhanced de novo fatty acid synthesis (FAS) activity, and fatty acids contributed to the cytoprotective effects of O‐GlcNAcylation under starvation. Moreover, dual inhibition of O‐GlcNAcylation and FASN displayed a strong synergistic effect in vitro in inducing cell death in cancer cells. Together, the results from this study provide novel insights into the role of O‐GlcNAcylation in the nutritional stress response and suggest the potential of combining inhibition of O‐GlcNAcylation and FAS in cancer therapy.